Juventude rural e sucessão familiar : o desafio da pedagogia da alternância nas casas familiares rurais - Fritz, Nilton Luiz (2012)
The object of this dissertation is to study the organization of the rural family homes and understand how these units can contribute to the construction of mechanisms that enable the family succession in small farms. In this study we analyze, understand and gain knowledge to assist, in particular, the leaders and representatives of the people to propose adjustments in public policy that meet the needs experienced by the rural population, reducing their fragility, increasing and enhancing the favorable factors for development of rural activity. The discussion of the succession of farms is a preoccupation for farmers and leaders. At this juncture, a significant portion of rural youth elects new places to live. Concomitantly, new players emerge for the development of agricultural and non-agricultural activities, and various public policies bolster the segment. The union leaders strive for the young woman and family farmers are more perceivable, considering they are responsible for producing approximately 70% of the foods that supply the tables of Brazilians. The training of rural youth, with the order of succession to farms, occupies more space in society agenda, a public policy that directly prepares schools are working with the Pedagogy of Alternation. The value family homes, discuss, empower youth and point solutions to issues pertaining to their stay in rural areas. We conducted 42 interviews with students, alumni, parents of students and teachers of the Rural Family House located in the municipality of Francisco Beltrão - Paraná. Finally, we point out suggestions that can be evaluated and considered for driving the process of succession of farms.